Surface morphology of composite from mahogany leaves waste with citronella oil (Cymbopogon winterianus Jowitt) as a natural coating for antifungal of Pleurotus ostreatus. Issue 2 (June 2021) - Masturi,; Alighiri, D; Drastisianti, A; Susilawati,; Fathurachman, Y; Maesaroh, S; Sunarno,
Abstract: In this work, citronella oil's activity as a natural coating for antifungal on mahogany's surface morphology (Swietenia mahagoni) leaves waste as composite was investigated. The composite material from mahogany leaves requires a coating that can inhibit fungi growth. Citronella oil was a natural material that can be used as an antifungal for coating this composite. The concentration of citronella oil used for the MIC (Minimum Inhibitory Concentration) assay was 0.1-2.0%. Based on the MIC of citronella oil can inhibit the growth of the fungus Pleurotus ostreatus at the optimum concentration of 0.2% with inhibition of 33.33%. Coating of citronella oil on composites using several concentrations ranging from 0.0, 0.4, 0.8, 1.2, 1.6 and 2%, respectively. The surface morphology on composite with citronella oil as the natural coating was observed using a CCD camera microscope with a magnification of 50x showed that the growth of fungal spores on the composite surface began to be inhibited a concentration of 0.4%. This surface morphology of composite can prove that citronella oil can be used as an antifungal.